Measurement of Chemical and Non-Chemical Parameters of Three Native Pistachio Cultivars of Damghan Region (Iran) for Studying Spring Frost - Afshari, Hossein; Hokmabadi, Hossein; Ebadi, Abdolghaphar; Laee, Ghanbar (Asian Journal of Chemistry, 2010)
Pistachio (Pistacia Vera L) is one of the most strategic products of Iran. Frost injury in recent years has exposed this product to serious risks. Determining the critical temperatures causing such damages in early spring, which are sometimes quite huge, has greatly contributed to developing and using timely prevention methods and measures aimed at reducing damages and may still be valuable in estimating inflicted losses caused by spring frost. A research project was undertaken at Islamic Azad University, Damghan Branch, in years 2007 and 2008. The experiment was conducted as factorial in a completely randomized design with two factors: cultivar type at three levels (Abbasali, Khanjari, Shahpasand) and temperature at five levels (+2, 0, -2, -4 and -6 °C) in three phases: growth of reproductive organs (swollen buds, opened flowers, newly fertilized fruits in late winter and early spring. Samples were places inside an incubator and temperature was reduced at a rate of 2 °C/h. At each temperature level some samples were taken out for studying the rate of damages. Also to determine the accumulation of proline and soluble sugars the samples were first treated and then measured in terms of proline and soluble sugar contents. Results indicated that the highest sensitivity to early spring cold was in the fully-opened flower stage and maximum damages were inflicted at -6 °C. Results also demonstrated that Abbasali and Shahpasand were the most and least resistant cultivars to spring frost, while Khanjari cultivar was recognized as semi-resistant.